The Local Identity that Still Survives - et. al., Simon Pieter Soegijono, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Self-identity is an affirmation activity or pinned behavior identity conducted in an institution. In every human life, various events are always attached to the attribute or identity carried. Generally, people in Ambon City have known this name and identity for generations. The qualitative research approach and case studies were used to demonstrate the Papalele people's identity strength and persisted to this day in society, even in their communities, this identity has been hereditary.